Earth and Vernacularity: Reviving vernacular architecture in Iceland with rammed earth construction - Gunnarsdóttir, Sunnefa (author) (2021)
The growing interest in rammed earth construction globally has yet to reach the Icelandic building industry which lags behind in sustainable construction methods. Despite the rich history of earth construction with local turf, standardized practices and imported materials dominate the building practice today. Earth is a readily available material in Iceland and is excavated in large quantities every year. This research aims to find a way to use the available earth in conjunction with other locally available materials to build more environmentally friendly and locally resourced buildings. No previous research could be found on rammed earth construction in the context of Iceland, therefore literature on rammed earth construction from other locations will be cited. A qualitative research will provide an overview of the materiality and social practices of both vernacular architecture and the development to standardized practices by relying on the relevant literature and an interview. Additional quantitative research gathers data on the flows of excavated earth. Finally, application proposals will be made with the materials studied. The findings of this research shows the great potential for earth construction in Iceland. Despite the vulnerability of earth construction in rough climates such as in Iceland, several uses could be found for the construction technique. Architecture, Urbanism and Building Sciences | Explorelab